Unveiling the Electrocatalytic Activity of Bifunctional Iron-Niobium Double Perovskites for Overall Water Splitting: A-Site Cation Influence - Avcioglu, Celal; Bekheet, Maged F.; Avcioglu, Suna; Kaya, Figen; Kim, Byung Chul; Kaya, Cengiz; Gurlo, Aleksander (WILEY, 2025)
Capitalizing on the electrochemical conversion of water into hydrogen stands as a pivotal strategy in the global transition toward sustainable energy sources. This study investigates the influence of the A-site cation type within A(2)FeNbO(6) double perovskites (where A = Ca, Sr, or Ba) on their bifunctional electrocatalytic activities. The electrocatalytic performance is scrutinized in relation to charge transfer resistance, oxygen vacancy concentration, and metal-oxygen covalency. Among the variants, Sr2FeNbO6 is distinguished as the optimal catalyst, achieving a current density of 10 mA cm(-2) at overpotentials of 260 mV for the oxygen evolution reaction (OER) and 176 mV for the hydrogen evolution reaction (HER), thus matching the performance of leading metal oxide electrocatalysts. The study reveals pH-dependent kinetics for Sr2FeNbO6, indicative of a lattice oxygen evolution mechanism for OER. An electrolyzer employing Sr2FeNbO6 electrodes for both the anode and cathode delivers a current density of 10 mA cm(-2) at an efficient cell voltage of 1.76 V for complete alkaline water splitting, while also demonstrating exceptional stability. These insights advance the understanding of material optimization for electrocatalysis and position Sr2FeNbO6 as a viable catalyst for the sustainable production of hydrogen.
Keywords: bifunctional catalysts; electrochemical hydrogen generation; HER; iron-niobium double perovskite; lattice oxygen evolution mechanism; OER; OXYGEN EVOLUTION; OXIDES; A(2)FENBO(6); CATALYSIS; SPECTRA; XPS; SR; Chemistry; Materials Science